(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Ramadan fasting presents significant physiological challenges for young football athletes, particularly regarding aerobic endurance due to energy deficits, dehydration, and altered recovery patterns. This study aimed to examine the effect of date extract supplementation on the endurance performance of U-15 football athletes during the fasting month. The study employed a quantitative experimental approach using a Pretest–Posttest Control Group Design. A total of 16 athletes from SSB Bhayangkara POP Semarang were selected and systematically divided into two groups: an experimental group (n = 8) receiving 30 ml of date extract during iftar for five consecutive days and a control group (n = 8) without supplementation. Aerobic endurance was measured using the Yo-Yo Intermittent Recovery Test Level 1, which demonstrated validity of r = 0.77 and reliability of 0.95. Data were analyzed using the Mann–Whitney U test at a 95% significance level. The pretest results indicated relatively balanced baseline endurance between the experimental group (12.73) and the control group (12.91). Following the intervention, the experimental group improved to 13.88, showing an increase of 1.15 points, whereas the control group slightly decreased to 12.83 (-0.08 points). The posttest mean difference between groups reached 1.05 points, with the experimental group obtaining a higher mean rank (10.69) than the control group (6.31). Statistical analysis produced U = 14.500, Z = -1.852, and p = 0.064 (>0.05), indicating no statistically significant difference. Nevertheless, the positive trend observed may be associated with the nutritional content of date extract, including antioxidants, vitamin C, and vitamin E, which potentially support glycogen recovery and reduce oxidative stress during fasting. Therefore, date extract may serve as a practical nutritional supplement for maintaining endurance performance in fasting football athletes.